Integrating Offshore Wind and Wave Resource Assessment - Pontes, M.T. (2009)
The aim of this paper is to review the sources of wind and wave information, the methodologies to assess offshore wind and wave energy resources, and the more relevant results at the European level as a first step to integration of the evaluation of both resources. In situ and remote sensed wind and wave data (using satellite based sensors) are done generally by distinct systems (except for SAR) but numerical atmospheric models and wind - wave models are closely related. Offshore wind resource studies using various types of data are reviewed especially in northern European seas and in the Mediterranean. The wave energy resource assessment at European and national levels is also reviewed and the various atlases are identified.